Arabic calligraphy as mosque decoration: architectural significance in Indonesia - Dariyadi, Moch Wahib; Murtadho, Nurul; Huda, Ibnu Samsul; Hassan, Abd Rauf (Springer Science and Business Media Deutschland GmbH, 2025)
This research investigates the significant role Arabic calligraphy performs in Indonesian mosque building. Arabic calligraphy is valued for both aesthetic and spiritual purposes; it is a required element of Islamic architectural expression. Analyzing the several calligraphic scripts, mostly Thuluth, Kufi, and Naskh, why these letters are chosen, and how they are incorporated into architectural features such domes, mihrabs, minbars, arches, and walls, the study analyzes at Emphasizing case studies of historically and culturally important mosques all throughout Indonesia, including in Java, Aceh, and South Kalimantan, the study employs a qualitative methodology. The results show that Arabic calligraphy not only improves the visual attractiveness of mosque exteriors and interiors but also provides a means of spiritual connection and cultural continuity, therefore preserving the religious identity of Muslim communities.